Ocular surface changes in mild and moderate myopes differing in duration of soft contact lens wear (Ukrainian Journal of Ophthalmology, 2026)
Background: Contact lenses (CL) are widely prescribed for various indications. A rather high incidence of severe complications in CL wearers necessitates a deeper and more detailed investigation of CL-associated ocular surface changes with duration of soft contact lens (SCL) wear.Purpose: To investigate ocular surface changes in mild and moderate myopes differing in duration of SCL wear.Materials and Methods: Seventy-nine mild and moderate myopes (152 eyes; mean age, 30.8±0.4 years; mean duration of lens wear, 10.2±0.6 years) wearing silicone hydrogel contact lenses were involved in the study. Patients were divided into groups based on duration of SCL wear (1-5 years, 6-10 years, and > 10 years). They completed an Ocular Surface Disease Index (OSDI) questionnaire and underwent visual acuity assessment, anterior biomicroscopy and the following tests: ocular surface fluorescein staining,   lid-parallel conjunctival folds (LIPCOF), lid-wiper epitheliopathy (LWE), fluorescein tear break-up time (FTBUT), Schirmer I and Schirmer II tests, and corneal sensation by the method of Faulkner using a cotton swab applicator. The van Bijsterveld system and the Baylor scale were used to quantify ocular surface staining and corneal staining, respectively.Results: In mild and moderate myopes wearing soft contact lenses, overall OSDI score, LIPCOF score, LWE score, FTBUT, Baylor corneal staining score, van Bijsterveld ocular surface fluorescein staining score, corneal sensation loss, presence of corneal epithelial edema, presence of corneal fluorescein staining, conjunctival hyperemia, presence and degree of limbal vascularization, presence and degree of corneal vascularization, and presence of corneal opacity were found to statistically significantly depend on duration of SCL wear.Conclusion: An OSDI test found mild ocular surface disease in myopic patients wearing lenses for ≤ 5 years, and moderate ocular surface disease, in those wearing lenses for > 5 years. There was a high probability of a severe corneal sensation loss (80%) for overall OSDI score ≥32.5 (i.e., moderate ocular surface disease). The most apparent changes in the ocular surface developed in patients wearing SCL for > 10 years. Decreased tear production and quality, lid-wiper epitheliopathy as shown by fluorescein staining, conjunctival folds (LIPCOF test), conjunctival hyperemia, corneal opacities, limbal and corneal vascularization were observed in patients wearing SCL for at least a year. Corneal edema and presence of corneal and conjunctival fluorescein staining were found in patients wearing SCL for at least 6 years. Loss of central corneal sensitivity was noted in patients wearing SCL for > 10 years.
Keywords: cornea; soft contact lenses; duration of lens wear; myopia